Analisis Pengaruh Disiplin Dan Motivasi Kerja Terhadap Produktivitas Kerja Karyawan Hotel Goodrich Suites Jakarta - Wendy Shelma Santika; Thyophoida W.S. Panjaitan (Fakultas Ekonomi Universitas Katolik Darma Cendika, 2023)
The existence of hotels in Indonesia is increasing every year. In line with theincreasing number of new hotels, the competition in the hotel industry is also getting tougher. Every hotel should be able to provide the best to the visitors. In an effort to realize this, it is very important to have employees who have good work productivity in an effort to achieve the goals set by the company. The purpose of this study was to determine the effect of discipline and work motivation on work productivity of the employees of the Hotel Goodrich Suites Jakarta. The population of this study were all employees of Hotel Goodrich Suites Jakarta, totaling 60 people and all populations were taken as samples. So the sample is a saturated sample or census. Based on the results of data processing with SPSS, it was found that all statement items for each variable were declared valid and all variables used in the study were declared reliable. The results of the classic assumption test consisting of the normality test, multicollinearity test, and heteroscedasticity test show that all of them fulfill. The multiple linear regression equation obtained is Y = 6.795 + 0.211 X1 + 0.189 X2. The Adjusted R Square value is 0.116 (11.6%), so it can be said that the contribution of work discipline and work motivation variables to work productivity for employees at the Goodrich Suites Hotel Jakarta is very low. Based on the results of the t test, it can be said that work discipline has a significant effect on the work productivity of Goodrich Suites Jakarta hotel employees, while work motivation has no effect on employee work productivity.